Pulse Narrowing and RF Linewidth Reduction of Integrated Passively Mode-Locked Laser in Anticolliding Design by Means of Spectral Tuning - V. Moskalenko; K. A. Williams; E. A. J. M. Bente (IEEE Photonics Journal, 2016)
In this paper, we present the first tunable extended cavity integrated passively mode-locked laser realized in an anticolliding design. The laser is realized as an InP-based photonic integrated circuit. A detailed study of the laser performance under various operating conditions is presented. The evolution of the radio-frequency (RF) spectrum and optical spectrum with the injection current to the optical amplifier is investigated. Tuning over 9 nm is achieved by injecting current in a distributed Bragg reflector section. We demonstrate that tuning of the optical spectrum toward shorter wavelengths, which increases absorption in the saturable absorber section, leads to an improvement of the mode-locked laser performance in terms of reduction of fundamental RF linewidth and reduction of the pulsewidths.